Exploring the Impact of Accelerated Thermal Aging on POME-Based MWCNT Nanofluid - Sharifah Masniah, Wan Masra; Yanuar Zulardiansyah, Arief; Siti Kudnie, Sahari; Ernieza, Musa; Andrew Ragai, Henry Rigit; Md Mizanur, Rahman (Springer Singapore, 2024)
This study aims to investigate the effects of accelerated thermal aging on modified refined, bleached, and deodorized (RBDPO) olein. Through a transesterification process, the RBDPO olein is converted into palm oil methyl ester (POME), which acts as the base fluid in the presence of conductive multi-walled carbon nanotube (MWCNT) at various concentrations. The accelerated aging is conducted at a temperature of 130 °C for 1000 h. Fourier transform infrared (FTIR) analysis reveals that the chemical composition of the aged nanofluids remains unchanged. The AC breakdown voltages of the aged nanofluids decrease as a result of the accelerated thermal aging over 1000 h, but they remain higher than those of the fresh POME.